Risks and threats as system-forming categories of state control and supervision - K. V. Maslov; A. S. Matnenko (Правоприменение)
The subject. The key characteristics of risks and threats in state control context are researched comprehensively.The purpose of the article is to confirm or disprove hypothesis that threats and risks should be the basis for determining the content of other elements of the system of state control and supervision.The methodology. The authors use the formal legal interpretation of normative acts, as well as systemic approach and analysis of philosophical literature, concepts of the security the-ory and monographs in different branches of law.The main results, scope of application. The relationship between the concepts of "threats" and "risks" is determined, and their author's definitions are proposed. A threat in control and supervisory activities is a set of events or acts that cause or are capable of causing damage to socially significant values. Risks are such threats to socially significant values, which are expressed in the actions of participants of social relations. Risks are associated with an incorrect assessment of the objective situation and can lead to harm with varying degrees of probability. The categories "risk" (in the negative aspect) and "threat" highlight two facets of the same entity. When describing malicious phenomena as threats, attention is focused on the possibility of causing harm as an integral attribute of such phenomena. Understanding them as risks allows us to give a quantitative description of the probability of occurrence of harmful consequences of the impact of a particular act on the protected object. Problems are identified in the reflection of the essential characteristics of risks and threats in the current legislation on state control (supervision) and in the new Federal Law of 31.07.2020 No. 248-FZ "On State Control (Supervision) and Municipal Control in the Russian Federation". The analysis of the Russian legislation shows that there is no comprehensive approach to fixing the essential characteristics of threats and risks, which are aimed at minimizing the control and supervisory activities. New Russian Law No. 248-FZ of 31.07.2020 also demonstrates that the legislator does not have a systematic approach to identifying risks and other threats and therefore effective measures to counteract their implementation through control and supervisory activities are not determined. The scientific substantiation of the characteristics of risks and threats in general allows both to enrich the theory of public control, and to improve the legislation on control and supervisory activities, as well as to increase the effectiveness of the protection of public interests in the process of its application.Conclusions. The key nature of threats and risks for determining other elements of the sys-tem of state control and supervision is substantiated The use of the term “threat" is preferred because of its more universal nature. Threats determines both the goals and principles of control and supervisory activities in any area, as well as its forms and methods.